The Biblical Politics of John Locke. By Kim Ian Parker. Pp. x + 201. (Editions SR, 29.) Waterloo, ON: Wilfrid Laurier University Press, 2004. isbn 0 88920 450 0. 59.95 - Pailin, David A. (The journal of theological studies, 2005)
Current political debates in the secular climate dominant in much of western Europe tend to become unsettled when arguments are presented on the basis of religious convictions, particularly if those presenting such convictions maintain that they express non-negotiable truths since they declare what God has revealed. They become even more unsettled if those with a contrary position claim that it is their contrary position that expresses the declared will of God. Rational consideration of the issues, whatever they may be, appears impossible when the appeal to human experience and rational reflection is frustrated by appeal to what is alleged to be higher, indeed supreme and infallible, authority.